Mechanisms for Temperature Modulation of Feeding in Goldfish and Implications on Seasonal Changes in Feeding Behavior and Food Intake - Chen, Ting; Wong, Matthew K. H.; Chan, Ben C. B.; Wong, Anderson O. L. (Frontiers in Endocrinology, 2019)
In fish models, seasonal change in feeding is under the influence of water temperature. However, the effects of temperature on appetite control can vary among fish species and the mechanisms involved have not been fully characterized. Using goldfish (Carassius auratus) as a model, seasonal changes in feeding behavior and food intake were examined in cyprinid species. In our study, foraging activity and food consumption in goldfish were found to be reduced with positive correlation to the gradual drop in water temperature occurring during the transition from summer (28.4 +/- 2.2 oC) to winter (15.1 +/- 2.6 oC). In goldfish with a 4-week acclimation at 28 oC, their foraging activity and food consumption were notably higher than their counterparts with similar acclimation at 15 oC. When compared to the group at 28 oC during summer, the attenuation in feeding responses at 15 oC during the winter also occurred with parallel rises of leptin I and II mRNA levels in the liver. Meanwhile, a drop in orexin mRNA along with concurrent elevations of CCK, MCH, POMC, CART and leptin receptor (LepR) transcript expression could be noted in brain areas involved in feeding control. In short-term study, goldfish acclimated at 28 oC were exposed to 15 oC for 24 hr and the treatment was effective in reducing foraging activity and food intake. The opposite was true in reciprocal experiment with a rise in water temperature to 28 oC for goldfish acclimated at 15 oC. In parallel time-course study with lowering of water temperature from 28 to 15 oC, short-term exposure (6-12 hr) of goldfish to 15 oC could also increase leptin I and II mRNA levels in the liver. Similar to our seasonality study, transcript level of orexin was reduced along with up-regulation of CCK, MCH, POMC, CART and LepR gene expression in different brain areas. Our results, as a whole, suggest that temperature-driven regulation of leptin output from the liver in conjunction with parallel modulations of orexigenic/anorexigenic signals and leptin responsiveness in the brain may contribute to the seasonal changes of feeding behavior and food intake observed in goldfish.